Job loss, credit card loans, and the college-persistence decision of US working students - Pinghui Wu; Lucy McMillan (Federal Reserve Bank of Boston, 2023)
This study assesses the impact of involuntary job loss on college persistence by leveraging different job-loss timings relative to a student's college enrollment decision. We find that job loss increases the probability that a working college student leaves college before attaining a degree, but access to short-term credit through credit card loans buffers this liquidity effect. By restricting credit supply to college students, the CARD Act of 2009 has inadvertently inhibited the ability of liquidity-constrained students to remain in college when their earnings unexpectedly fall, resulting in a stronger liquidity effect of job loss on college persistence over the last decade.
Keywords: I22; I23; J64; 330; Credit card loans; unemployment; college persistence